Do urban regeneration programmes improve public health and reduce health inequalities? A synthesis of the evidence from UK policy and practice (1980–2004). Issue 2 (13th January 2006) - Thomson, Hilary; Atkinson, Rowland; Petticrew, Mark; Kearns, Ade
Abstract : Objectives: To synthesise data on the impact on health and key socioeconomic determinants of health and health inequalities reported in evaluations of national UK regeneration programmes. Data Sources: Eight electronic databases were searched from 1980 to 2004 (IBSS, COPAC, HMIC, IDOX, INSIDE, Medline, Urbadisc/Accompline, Web of Knowledge). Bibliographies of located documents and relevant web sites were searched. Experts and government departmental libraries were also contacted. Review methods: Evaluations that reported achievements drawing on data from at least two target areas of a national urban regeneration programme in the UK were included. Process evaluations and evaluations reporting only business outcomes were excluded. All methods of evaluation were included. Impact data on direct health outcomes and direct measures of socioeconomic determinants of health were narratively synthesised. Results: 19 evaluations reported impacts on health or socioeconomic determinants of health; data from 10 evaluations were synthesised. Three evaluations reported health impacts; in one evaluation three of four measures of self reported health deteriorated, typically by around 4%. Two other evaluations reported overall reductions in mortality rates. Most socioeconomic outcomes assessed showed an overall improvement after regeneration investment; however, the effect size was often similar to national trends. In addition, some evaluations reported adverse impacts. Conclusion: There is little evidence of the impact of national urban regeneration investment on socioeconomic or health outcomes. Where impacts have been assessed, these are often small and positive but adverse impacts have also occurred. Impact data from future evaluations are required to inform healthy public policy; in the meantime work to exploit and synthesise "best available" data is required.